Multisensory Stimulation in Stroke Rehabilitation - Johansson, Barbro B. (Frontiers in Human Neuroscience, 2012)
The brain has a large capacity for automatic simultaneous processing and integration of sensory information. Combining information from different sensory modalities facilitates our ability to detect, discriminate, and recognize sensory stimuli, and learning is often optimal in a multisensory environment. Currently used multisensory stimulation methods in stroke rehabilitation include motor imagery, action observation, training with a mirror or in a virtual environment, or various kinds of music therapy. Several studies have shown positive effects been reported but to give general recommendation more studies are needed. Patient heterogeneity and the interactions of age, gender, genes and environment are discussed. Randomized controlled longitudinal trials starting earlier post stroke are needed. The advance in brain network science and neuroimaging enabling longitudinal studies of structural and functional networks are likely to have an important impact on patient selection for specific interventions in future stroke rehabilitation.